Characterization of slag fines for use as a dredged material amendment - Wazne, M. (2017)
This study presents the results of an evaluation of 3/8-inch minus steel slag fines (SSF) and blast furnace fines (BFF) generated at the Severstal Steel Mill at Sparrows Point (Baltimore, MD), as potential geo-environmental enhancement to dredged material (DM) to make blended synthetic fills for the urban, coastal construction fill market. Visually, the SSF and BFF materials resemble an AASHTO No. 9 aggregate, with a small fraction passing the No. 200 (0.75 mm) sieve. Both types of fines appear to hold promise for blending with DM from a geotechnical enhancement (coarse-grained) and environmental (residual lime/cementation) perspective to provide strength and immobilization of heavy metals in a single material. The following geochemical attributes are compared: bulk chemistry, pH, and total priority pollutant list (PPL) metals. The following geotechnical parameters are evaluated: soil classification and grain size distribution, specific gravity, loss on ignition (ash content), standard and modified Proctor compaction behavior, and direct shear strength. These data were used to select one source of slag fines for full project rollout.